An investigation into stylistic devices used in “the grapes of wrath” by john steinbeck and their vietnamese translational equivalents - Nguyễn, Thị Ngọc Yến (ĐHNN, 2016)
This thesis was done in an effort to investigate the Stylistic Devices Used in “The Grapes of Wrath” by John Steinbeck and Their Vietnamese Translational Equivalents. The four stylistic devices under investigation were collected from the novel ―The Grapes of Wrath‖ by John Steinbeck. A combination of research methods was used for this thesis such as descriptive method, qualitative and quantitative method. As regards the data corpus, a total of 300 samples in term of stylistic devices in English and Vietnamese translation were collected. The findings of this thesis show that in both English and Vietnamese versions, simile plays the most important role, then repetition, metaphor and the last one is hyperbole. They have served as a foundation for the researcher to put forward some implications for the teaching and learning of writing. In addition, this thesis can be used as a reference for teachers, learners or those who are interested stylistic devices and can provide them with a better understanding of using stylistic devices.
Keywords: stylistic devices